Ethical mindsets: an Australian study - Issa, Theodora; Pick, David (Springer Netherlands, 2010)
The aim of this article is to define and delineate an ethical mindset. In deploying an interpretive mixed-methods analysis of the Australian services sector, data were collected through an online survey on 223 respondents followed by focus group interviews involving 20 participants. The analysis reveals evidence of ethical mindsets in Australian business context, the components of which are identified as being aesthetic judgement, spirituality, optimism, harmony and balance, contentment, truth telling, individual responsibility and professionalism. While the findings are limited to the Australian context, it illuminates the value of mindsets to business ethics in a way that has theoretical rigour and practical relevance. Research has so far only considered business ethics within other mindsets (e.g. global mindset). This article provides a foundation for further application and development of mindset theory.